The Effect Of Good Corporate Governance and Company Size On Tax Avoidance (Empirical Study On Agricultural Sector Companies Listed On The Indonesia Stock Exchange For The Period 2017-2019) - Reva Mega Arandea (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of good corporate governance, institutional ownership proxies, the proportion of independent boards of commissioners, and audit committees, as well as company size on tax avoidance in agricultural sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The samples used in this study were obtained by purposive sampling method and the analysis techniques used were by descriptive statistical analysis, multiple linear analysis, classical assumption test, and hypothesis test. The results of this study show that partially institutional ownership and the proportion of independent board of commissioners have no influence on tax avoidance proxied by the CETR formula, while the audit committee has a negative influence on tax avoidance proxied by the CETR formula, and company size has a positive influence on tax avoidance proxied by the CETR formula. Simultaneously, institutional ownership, the proportion of independent board of commissioners, audit committee, and company size have a significant positive influence on tax avoidance proxied by the CETR formula.